Medical Use of Intelligent Systems - Rita Komalasari (Lambung Mangkurat, 2023)
This essay delves into the ethical implications of integrating artificial intelligence (AI) into medical practice, addressing a critical gap in the existing research. As AI-driven medical systems have gained prominence over the past decade, there is an urgent need to explore the moral dimensions of their utilization. This study holds significant relevance for academics, healthcare professionals, and policymakers, especially those involved in intelligent medical systems. The exploration begins by dissecting the moral dilemmas surrounding AI applications in healthcare, exploring both technological justifications and concerns. The paper evaluates existing taxonomies developed by researchers in the field, shedding light on the issues that emerge during the development of intelligent medical systems. By scrutinizing the ethical reasons behind healthcare practitioners' adoption of intelligent systems, this research contributes valuable insights for a comprehensive understanding of the subject. This analysis not only informs scholars but also provides crucial guidance to government officials and medical professionals navigating the intricate landscape of AI in medicine.